Screening Cuba : Film Criticism as Political Performance during the Cold War - Amaya, Hector (Book collections on Project MUSE., 2010)
In examining cultural production through the lens of the Cold War, Amaya reveals how contrasting interpretations by Cuban and U.S. critics are the result of the political cultures in which they operated. While Cuban critics viewed the films as powerful symbols of the social promises of the Cuban revolution, liberal and leftist American critics found meaning in the films as representations of anti-establishment progressive values and Cold War discourses. By contrasting the hermeneutics of Cuban and U.S. culture, criticism, and citizenship, Amaya argues that critical receptions of political films constitute a kind of civic public behavior"--Publisher